Effect of Vacuum Packaging On Sensory and Texture Properties of Fresh Cut Jackfruit - ASMADY, NURUL HUSNA; ZAINAL ABIDIN, MUNIRA (Enhanced Knowledge in Sciences and Technology, 2023)
Jackfruit, also known as Artocarpus heterophyllus, is a fruit from a tropical tree that is raised in South America, Africa, and Asia. Jackfruit is typically eaten raw in Malaysia. Vacuum packaging, on the other hand, describes the process of taking the air out of the packaging before closing the product. Vacuum packaging’s primary goal is to stop a product’s oxidation reaction when the product is exposed to oxygen [1]. Freshly cut jackfruit that is often packaged in plastic is vulnerable to tissue softening, surface browning, and flavor loss. As a result, the goal of this research is to examine how vacuum packaging affects the sensory and textural characteristics of freshly sliced jackfruit. There are three samples in this study which was control sample (vacuum packed), vacuum packed and unvacuum packed which were dipped in 1% CaCl2 solution for 5 minutes. The sample then was stored for 15 days at temperature of 4 oC. The pH value for the vacuum packed sample on day 15 was 4.89 ± 0.01. The vacuum packed sample experienced the least moisture loss during storage among the three samples. The experiment’s results for the sample’s brightness, chroma, and hue were not significant (p>0.05), however the results for the sample’s firmness were significant since (p<0.05). According to the sensory study, the vacuum-packed sample is the most palatable of the three.